Exo-Glove Poly II: A Polymer-Based Soft Wearable Robot for the Hand with a Tendon-Driven Actuation System - Kang, Brian Byunghyun; Choi, Hyungmin; Lee, Haemin; Cho, Kyu-Jin (Soft robotics, 2019)
This article presents Exo-Glove Poly (EGP) II, a soft wearable robot for the hand with a glove that is completely constructed of polymer materials and that operates through tendon-driven actuation for use in spinal cord injury (SCI). EGP II can restore the ability to pinch and grasp any object for people with SCI in daily life. The design of the glove allows it to be compact and extends the range of hand sizes that can fit. A passive thumb structure was developed to oppose the thumb for improved grasping. To increase the robustness of the glove, EGP II was designed to have a minimal number of components using a single material. A kinematic model of the system was used to optimize the design parameters of an antagonistic tendon routing system on a single actuator for various hand sizes and repeated actuations. Experiments were conducted on two subjects with SCI to verify the grasping performance of EGP II. EGP II has a compact glove and an actuation system that can be placed on a desk or wheelchair, with the weights of 104 g and 1.14 kg, respectively.